Professional migration from the United States to Europe: Composite vignettes of black male basketball players from underserved communities. (May 2021) - Book, Robert T.; Stambulova, Natalia; Henriksen, Kristoffer
Abstract: Objective: To explore how the intersectional perspective of being a Black male from an underserved community shaped the professional cultural transition of American basketball players to Europe. Design: and Method : The seven Black male athletes, who met the criteria of playing at least one year in a professional European basketball league and spending their formative years in an underserved community in the USA, participated in this study. Life story interviews, lasting between one and 2 h, were analysed through the principles of narrative analysis. Creative non-fiction was used to represent the findings in the form of composite vignettes using the words of the participants to create an evocative and meaningful experiential reconstruction. Findings: The analysis uncovered three primary themes; steppingstones to becoming a professional basketball migrant; from America to Europe: a whole new world once again; and "don't bother to unpack your bags:" from ups and downs to settlement plans. Within these themes, the intersectional identity of being a Black male from a poor community underpinned the storyline. Conclusions: All seven participants left their underserved community at some point during their teenage years, and this transition into a more affluent, White dominated society proved beneficial for the move to Europe. Further, the shared intersectional identity of being an African American male from a low socioeconomic community had critical implications for how they experienced the cultural transition to Europe, and how they were received by the host environment. Highlights: We explore the cultural transition of 7 Black American basketball players to Europe. Composite vignettes merge the participants' experiences into a collective narrative. Moving to Europe was the athletes second significant cultural transition in life. The intersection of race and poverty prominently influenced the athletes' narratives. Cultural transitions have a temporal dynamic that should be considered.